2019
DOI: 10.1093/jnci/djz078
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Role of RNA-Binding Protein hnRNP K in B-Cell Lymphomas

Abstract: BackgroundHeterogeneous nuclear ribonucleoprotein K (hnRNP K) is an RNA-binding protein that is aberrantly expressed in cancers. We and others have previously shown that reduced hnRNP K expression downmodulates tumor-suppressive programs. However, overexpression of hnRNP K is the more commonly observed clinical phenomenon, yet its functional consequences and clinical significance remain unknown.MethodsClinical implications of hnRNP K overexpression were examined through immunohistochemistry on samples from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“… 129 However, another study found that hnRNPK is overexpressed in diffuse large B-cell lymphoma patients without Myc genomic alterations, representing a mechanism of C-Myc activation without Myc lesions, due to hnRNPK overexpression. 130 In addition, the overexpression of hnRNPK can promote lung metastasis, 131 and the increased hnRNPK expression is observed in multiple types of cancer, including breast, prostate, colorectal, gastric and pancreatic cancers. 132 Therefore, considering the inhibition of tumor cell growth by hnRNPK as a haploinsufficient tumor repressor in myeloid malignancies, 133 it is tempting to speculate that the dichotomous roles of hnRNPK in tumorigenesis may reflect the diverse hnRNPK functions in different cellular contexts.…”
Section: Alterations Of Splicing Regulatory Factors and Related Signamentioning
confidence: 99%
“… 129 However, another study found that hnRNPK is overexpressed in diffuse large B-cell lymphoma patients without Myc genomic alterations, representing a mechanism of C-Myc activation without Myc lesions, due to hnRNPK overexpression. 130 In addition, the overexpression of hnRNPK can promote lung metastasis, 131 and the increased hnRNPK expression is observed in multiple types of cancer, including breast, prostate, colorectal, gastric and pancreatic cancers. 132 Therefore, considering the inhibition of tumor cell growth by hnRNPK as a haploinsufficient tumor repressor in myeloid malignancies, 133 it is tempting to speculate that the dichotomous roles of hnRNPK in tumorigenesis may reflect the diverse hnRNPK functions in different cellular contexts.…”
Section: Alterations Of Splicing Regulatory Factors and Related Signamentioning
confidence: 99%
“…Cells were homogenized in NP40 lysis buffer and standard immunoblotting procedures performed as previously described (Gallardo et al, 2019) using antibodies against hnRNP K (3C2), RUNX1 (EPR3099, both from Abcam, Cambridge, MA), β-actin (AC-15, Santa Cruz Biotechnology, Dallas, TX), Flag (F1804, Sigma Aldrich), HSP90 (ADI-SPA-836-D, Enzo Life Sciences)…”
Section: Methodsmentioning
confidence: 99%
“…As described previously (Gallardo et al, 2019), a computer-based algorithm was used that scan transcripts of interest for two or more (U/C)CCC motifs within 19 nucleotides.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations